Formação profissional continuada com professores que ensinam Matemática: um estudo sobre os elementos que caracterizam o desenvolvimento de uma coletividade - Rodrigues, Carolina Innocente (Universidade Federal de São Carlos, 2020)
This research aims to investigate which elements, from the perspective of the HistoricalCultural Theory and through the theoretical studies of the community, could be verified during the continuing professional training course taught to 20 Mathematics teachers of Basic Education, in the period from August to December 2017. Therefore, the question that leads it is: What elements can characterize the development of a group of teachers who teach mathematics to constitute themselves as a collective in a formative scenario? We assume as a collective concept, an organized group of free workers willing to develop based on common goals and needs, in a harmonious relationship liable to successes and failures, however, without neglecting personal goals. The research was developed from a context of continuing professional training, based on the qualitative approach and on the methodological principles arising from the dialectical historical materialist method. Defending the thesis that continuing professional training courses, when organized theoretically and methodologically as an activity in the perspective of historical-cultural theory, are configured as formative spaces for a collective in the Brazilian educational scenario. For that, we consider the observation and participation in the apprehension of the production of the reality experienced by the group, valuing, for the analyzes, the contradictions as fundamental. The analyzes were constructed by means of four essential elements, characterized as formative: 1) Collectivity, 2) Work, 3) Organization 4) Consciousness and Alienation. As a result, it was possible to expand the knowledge about the collective and the continuing professional education in Brazil based on the systematization of the elements that constitute the development of a collective of teachers, so that this training process is not depreciated only for career advancement. Furthermore, to give light to a structure of continuing professional training with teachers through HistoricalCultural Theory, and in the social, political and economic scenario in which we live, enable us to work from a more human perspective in favor of the constitution of an educational collectivity.
Continuing professional training with teachers who teach Mathematics: a study on the elements that characterize the development of a collectivity
Keywords: Coletividade; Trabalho; Formação profissional continuada; Formação de professores que ensinam Matemática; Teoria Histórico-Cultural; Collectivity; Work; Continuing professional training; Training of teachers who teach mathematics; Historical-Cultural Theory; CIENCIAS HUMANAS::EDUCACAO